2023
DOI: 10.4239/wjd.v14.i9.1422
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of traditional Chinese medicine for diabetic retinopathy: A systematic review and network meta-analysis of randomized clinical trials

Hong-Dian Li,
Ming-Xuan Li,
Wen-Hua Zhang
et al.

Abstract: Diabetes and associated complications represent major global public health issues which are associated with impaired quality of life and premature death. Although some diabetic complications have decreased in the developed world, the majority are still prevalent, with an increasing trend in the developing world. Currently used therapies are mainly ‘glucocentric’, focusing on the optimization of glycemic control to prevent, delay or manage diabetes-associated complications- other common comorbidities, such as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 160 publications
0
1
0
Order By: Relevance
“…Its efficacy in DR treatment may be attributable to the synergistic effects of multiple active ingredients engaging in different biological targets and pathways [ 182 ]. Furthermore, a meta-analysis by Li et al, comparing the effects of combining traditional Chinese medicine and conventional Western medicine treatment for DR, showed that combining therapies could lower blood glucose levels, improve fundus hemorrhage, and restore visual function in DR patients [ 183 ].…”
Section: Mechanisms Of Action Toxicity and Drug–drug Interactions Of ...mentioning
confidence: 99%
“…Its efficacy in DR treatment may be attributable to the synergistic effects of multiple active ingredients engaging in different biological targets and pathways [ 182 ]. Furthermore, a meta-analysis by Li et al, comparing the effects of combining traditional Chinese medicine and conventional Western medicine treatment for DR, showed that combining therapies could lower blood glucose levels, improve fundus hemorrhage, and restore visual function in DR patients [ 183 ].…”
Section: Mechanisms Of Action Toxicity and Drug–drug Interactions Of ...mentioning
confidence: 99%